8 PHEOCHROMOCYTOMA-INDUCED CARDIOMYOPATHY. (1st January 2006) - Dale, D.; Matthews, V.; Gomez-Sanchez, C.
Abstract : Pheochromocytomas have multiple presenting manifestations including hypertension or the classic triad of headaches, palpitations, and diaphoresis. Other rare presenting manifestations include pulmonary edema, ECG changes, and/or a catecholamine-induced cardiomyopathy, which has been found to be reversible after treatment with either alpha-receptor blockading agents or tumor removal. A 27-year-old African American man presented with the complaint of a neck mass for which an FNA was performed. Later in the evening he presented to an outside ER with acute pulmonary edema requiring intubation. His blood pressure was found to be in the 200 s/120 s, and he was found to have ECG changes of ST depressions in V4-V6 with a troponin elevation to 6.48. An echo revealed an EF of 10-20% with global hypokinesis. Two days later he was transferred to our facility. Upon questioning of his family, the patient's mother gave a history of HTN with removal of tumors of bilateral adrenal glands. Included in his differential diagnosis was pheochromocytoma, so plasma metanephrines were ordered. Renal ultrasound revealed bilateral adrenal masses. The pathology of the thyroid mass returned with the differential diagnosis including hyperplastic goiter or neoplastic process, so with the above history a calcitonin level was ordered. When his blood pressure again increased to 190/100 s, he was given a phentolamine infusion challenge with improvement in his blood pressure to 150 s/70 s. The patient was subsequently started on oral phenoxybenzamine. Two weeks after his initial presentation, his calcitonin returned at the level of 11, 420. His plasma metanephrines returned at 25.3 (normal 0-0.49), with normetanephrines returning at 87 (normal 0-0.89). Genetic testing revealed a mutation in codon 634 of the RET proto-oncogene. Bilateral adrenalectomy was performed revealing pheochromocytomas and a total thyroidectomy revealed medullary thyroid cancer. Before bilateral adrenalectomy, repeat echo performed 3 weeks after initial presentation revealed normalization of cardiac function with an EF of 60% after alpha receptor blockading agents were used for treatment. Pheochromocytomas may rarely present with catecholamine-induced myocarditis or cardiomyopathy. The pathogenesis of catecholamine-induced cardiomyopathies has many factors: an increase in calcium influx, oxidized products of catecholamines, reduction in cardiac function by down-regulation of receptors, and also coronary vasoconstriction. The cardiomyopathy has been shown to be of the dilated and hypertrophic types. It has been found to be reversible after medical treatment with the alpha receptor blockading agents and also after the resection of the pheochromocytoma.